Glacial–interglacial Nd isotope variability of North Atlantic Deep Water modulated by North American ice sheet - Zhao, Ning; Oppo, Delia W.; Huang, Kuo-Fang; Howe, Jacob N. W.; Blusztajn, Jerzy; Keigwin, Lloyd D. (Nature Communications, 2019)
The Nd isotope composition of seawater has been used to reconstruct past changes in the contribution of different water masses to the deep ocean. In the absence of contrary information, the Nd isotope compositions of endmember water masses are usually assumed constant during the Quaternary. Here we show that the Nd isotope composition of North Atlantic Deep Water (NADW), a major component of the global overturning ocean circulation, was significantly more radiogenic than modern during the Last Glacial Maximum (LGM), and shifted towards modern values during the deglaciation. We propose that weathering contributions of unradiogenic Nd modulated by the North American Ice Sheet dominated the evolution of the NADW Nd isotope endmember. If water mass mixing dominated the distribution of deep glacial Atlantic Nd isotopes, our results would imply a larger fraction of NADW in the deep Atlantic during the LGM and deglaciation than reconstructed with a constant northern endmember.